Development of a Mycobacterium smegmatis transposon mutant array for characterising the mechanism of action of tuberculosis drugs: Findings with isoniazid and its structural analogues. Issue 4 (July 2015) - Campen, Richard L.; Ackerley, David F.; Cook, Gregory M.; O'Toole, Ronan F.
Summary The development of new drugs is required to control human tuberculosis (TB). This study examined whether drug hypersensitive mutants could be used to reveal novel aspects of the mechanism of action of a TB drug. A transposon mutant collection with an estimated 1.1-fold genome coverage (7680 mutants) was constructed in Mycobacterium smegmatis and screened in high-throughput against isoniazid. Hypersensitive transposants with mutations in genes known to influence the mode of action of isoniazid were isolated. To further investigate the role of one of these genes, nudC, the corresponding mutant was tested for sensitivity towards isoniazid structural analogues. Overexpression of nudC, as well as inhA which encodes a known target of isoniazid, increased M. smegmatis resistance to isoniazid, but failed to increase resistance to three of the analogues, NSC27607, NSC33759, and NSC40350. In contrast, overexpression of katG resulted in increased sensitivity to each of the isoniazid analogues tested including NSC27607, NSC33759, and NSC40350. This provides evidence that the latter isoniazid analogues are activated by KatG in a NudC-independent manner and that InhA may not be their primary target. In summary, characterisation of drug hypersensitive mutants detected genes involved in the mode of action of isoniazid. Furthermore, it identified isoniazid analogues which are resilient to both InhA- and NudC-dependent mechanisms of resistance.